2006
DOI: 10.1111/j.1365-2761.2006.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a lethal protease in the extracellular products of Vibrio splendidusVibrio lentus related strains

Abstract: The presence of a lethal extracellular 39-kDa protease, a virulence determinant of a Listonella pelagia strain which produces vibriosis in turbot, was determined in the extracellular products (ECP) of 33 Vibrionaceae strains. Both immunological and enzymatic techniques distinguished this specific protease from other Vibrionaceae proteins. It was detected in 15% (5/33) of the ECPs assayed belonging to strains of the Vibrio splendidus-V. lentus related group isolated in Galician aquaculture systems (NW Spain). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Hitherto, V. splendidus has been associated with disease outbreaks in molluscs (Gay, Ranault, Pons & Le Roux 2004; Gómez‐León, Villamil, Lemos, Novoa & Figueras 2005), but most reports from fish deal with hatchery‐reared larvae (Sedano, Zorrilla, Moriñigo, Balebona, Vidaurreta, Bordas & Borrego 1996; Gatesoupe, Lambert & Nicolas 1999; Thomson, Macpherson, Riaza & Birkbeck 2005). Although some V. splendidus strains have been associated with diseased juvenile‐cultured turbot and cod (Angulo, López & Vicente 1994; Santos, Pazos, Núñez & Toranzo 1997), their virulence is variable and recent attempts to experimentally induce mortality with some of them in turbot have failed (Farto, Armada, Montes, Pérez & Nieto 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hitherto, V. splendidus has been associated with disease outbreaks in molluscs (Gay, Ranault, Pons & Le Roux 2004; Gómez‐León, Villamil, Lemos, Novoa & Figueras 2005), but most reports from fish deal with hatchery‐reared larvae (Sedano, Zorrilla, Moriñigo, Balebona, Vidaurreta, Bordas & Borrego 1996; Gatesoupe, Lambert & Nicolas 1999; Thomson, Macpherson, Riaza & Birkbeck 2005). Although some V. splendidus strains have been associated with diseased juvenile‐cultured turbot and cod (Angulo, López & Vicente 1994; Santos, Pazos, Núñez & Toranzo 1997), their virulence is variable and recent attempts to experimentally induce mortality with some of them in turbot have failed (Farto, Armada, Montes, Pérez & Nieto 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental infections with the different serotypes of the two species are necessary to reveal their actual virulence. In addition, the possible involvement of lethal proteases, as reported for some V. splendidus ‐related strains (Farto et al 2006), should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes damage the extracellular matrix of animals and thus are important both for tissue colonization and nutrients supply. In a study of the fish pathogen F. columnare , a chondroitin lyase was found to be related to the virulence (Suomalainen et al, 2006). Plant and algal pathogens are able to degrade cell wall compounds such as pectins and agars.…”
Section: The Phylum Bacteroidetesmentioning
confidence: 99%
“…The presence of a lethal extracellular 39-kDa protease, similar to that of Vibrio pelagius , was detected in 15% of the ECP assayed belonging to strains of the Vibrio splendidus – V. lentus related group by Farto et al (2006), which suggested their potential risk for the health of reared aquatic organisms.…”
Section: New Vibrio Species Associated To Molluscsmentioning
confidence: 99%